2020
DOI: 10.3389/fpsyt.2020.00741
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Necrosis After Binge Eating in Bulimia: Recovery From Eating Disorder After Total Gastrectomy

Abstract: Background Gastric necrosis following acute gastric dilatation is rare but more common in females with eating disorders, such as anorexia nervosa or bulimia, during which patients often alternate restriction and binge eating behaviors. Case Presentation A 37-year old female patient with a history of 15 years of bulimia nervosa was admitted to the emergency department 24 h after binge eating. Abdominal Computed Tomography imaging showed major gastric distension reaching … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
1
1
0
Order By: Relevance
“…Similar conclusions have been reached by Achamrah et al. 4 which have shown that AGD with subsequent gastric necrosis can occur especially in patients that often alternate restriction and binge-eating behaviours. The authors also pointed out that starvation may induce atony of the stomach which is, therefore, more prone to rupture after overeating.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Similar conclusions have been reached by Achamrah et al. 4 which have shown that AGD with subsequent gastric necrosis can occur especially in patients that often alternate restriction and binge-eating behaviours. The authors also pointed out that starvation may induce atony of the stomach which is, therefore, more prone to rupture after overeating.…”
Section: Discussionsupporting
confidence: 88%
“…Binge eating is more common in women with an estimated prevalence of 4.9% in the female population. 2 Rarely, in such cases an Acute Gastric Dilatation (AGD) results; this complication is more frequent in binge anorexia nervosa/purge subtype and in bulimia nervosa 3,4 and can cause stomach rupture, when urgent surgery is required, which may prevent the death of the patient, also inducing a clinical recovery, but mortality is very high. 4,5 There are no reported cases of death caused by stomach rupture related to a single episode of binge eating in people unaffected by anorexia nervosa or bulimia nervosa.…”
Section: Introductionmentioning
confidence: 99%